Violation of the 12/23 rule of genomic V(D)J recombination is common in lymphocytes - Parkinson, Nicholas J.; Roddis, Matthew; Ferneyhough, Ben; Zhang, Gang; Marsden, Adam J.; Maslau, Siarhei; Sanchez-Pearson, Yasmin; Barthlott, Thomas; Humphreys, Ian R.; Ladell, Kristin; Price, David A.; Ponting, Chris P.; et al. (Genome Research, 2015)
V(D)J genomic recombination joins single gene segments to encode an extensive repertoire of antigen receptor specificities in T and B lymphocytes. This process initiates with double-stranded breaks adjacent to conserved recombination signal sequences that contain either 12- or 23-nucleotide spacer regions. Only recombination between signal sequences with unequal spacers results in productive coding genes, a phenomenon known as the “12/23 rule.” Here we present two novel genomic tools that allow the capture and analysis of immune locus rearrangements from whole thymic and splenic tissues using second-generation sequencing. Further, we provide strong evidence that the 12/23 rule of genomic recombination is frequently violated under physiological conditions, resulting in unanticipated hybrid recombinations in ∼10% of Tcra excision circles. Hence, we demonstrate that strict adherence to the 12/23 rule is intrinsic neither to recombination signal sequences nor to the catalytic process of recombination and propose that nonclassical excision circles are liberated during the formation of antigen receptor diversity.